Identification of okra shoot and fruit borer infesting okra and their distribution in Bangladesh (Bangladesh Journal of Agricultural Research, 2016)
A survey was conducted during July 2009 to October 2010 to know the occurrence of okra shoot and fruit borer species that infest okra in Bangladesh. Infested okra fruits were collected from eleven selected locations representing 11 Agro-ecological Zones of Bangladesh and reared in the laboratory. A total of 423 adult individuals consisting of 188 male and 235 female moths emerged from the infested fruits. The male and female ratio was 1.00?1.25. The morphological characteristics of adult moths were recorded. Head and thorax of adults are ochreous white; forewings are pale white with a wedge shaped horizontal green patch in the middle and hind wings are silvery creamy white in color. The males are smaller than the females in size and the females are Vshaped at the end of the anal part but the males have thick hairs at the end of the anal part. Pupae are chocolate brown, bluntly rounded and enclosed in grey colored inverted boat shaped cocoon formed in the fruit or in the sand. Full grown caterpillars measured 1.64 cm in length and their color is brownish with white streaks dorsally and pale yellow ventrally, without finger tipped process. The recorded morphological characteristics ware compared with standard key and the insects were identified as Earias vittella belonging to the family Noctuidae.Bangladesh J. Agril. Res. 41(4): 657-665, December 2016